SYNTAXY OF TITANITE, AEGIRINE AND ECKERMANNITE IN ALKALI SYENITE PEGMATITES OF THE VISHNEVYE MOUNTAINS (SOUTH URALS) - V.A. Popov; I.A. Blinov; V.I. Popova (Минералогия)
Crystallographic orientation of titanite intergrowths with aegirine and eckermannite was found in alkali syenite pegmatites of the Vishnevye Mountains: the titanite face ( 1 11) is parallel to pyroxene and amphibole face (010) and the titanite face (110) is parallel to pyroxene face (110). Aegirine is a host mineral for oriented intergrowths of titanite and eckermannite and chaotic inclusions of feldspar, apatite-(F), monazite-(Ce), hydroxycalciopyrochlore, lantanite-(Ce), zircon, rutile, pyrite, galena and barite. Pyrite is characterized by oriented intergrowths which calcite crystals: the axis L3 of pyrite and calcite is parallel and pyrite face (100) is parallel to calcite face (10 1 1). Eckermannite, hydroxycalciopyrochlore and lantanite-(Ce) were found for the first time in pegmatites of the Vishnevye Mountains.